Contrast-Induced Neurotoxicity following Cardiac Catheterization. (6th November 2012) - Law, Susan; Panichpisal, Kessarin; Demede, Melaku; John, Sabu; Marmur, Jonathan D.; Nath, Jaya; Baird, Alison E.
Abstract : We report a case of probable contrast-induced neurotoxicity that followed a technically challenging cardiac catheterization in a 69-year-old woman. The procedure had involved the administration of a large cumulative dose of an iodinated, nonionic contrast medium into the innominate artery: twelve hours following the catheterization, the patient developed a seizure followed by a left hemiplegia, and an initial computed tomography (CT) scan showed sulcal effacement in the right cerebral hemisphere due to cerebral swelling. The patient's clinical symptoms resolved within 24 hours, and magnetic resonance imaging at 32 hours showed resolution of swelling. Contrast-induced neurotoxicity should be found in the differential diagnosis of acute neurological deficits occurring after radiological procedures involving iodinated contrast media, whether ionic or nonionic.